Development of an integrated environment for the reengineering of public sector e-government system processes. (31st August 2005) - Michaelides, Roula; Kehoe, Dennis
This paper describes a case study-based research project in a North Wales Social Services department, aiming at transforming the core business processes from manual paper-based systems to transparent web-based applications. There is an emphasis on the structured approach used when developing the portal prototype, which incorporated a business process automation component with a view of meeting the e-government agenda. This paper reviews current systems used in the public sector and proposes the development of an e-government system supporting an integrated environment. The proposed system leverages on the internet to provide portable systems based on data transparency and process integration through portal technologies.